Sistem Informasi Pengajuan Proposal dan Lembar Pertanggungjawaban Berbasis Web pada Biro Administrasi Kemahasiswaan dan Alumni Universitas Kristen Petra - Pratama, Frandy Arista; -, Yulia; Gunawan, Denny (Jurnal Infra, 2015)
Student activities is an activity that is often performed by students of Petra Christian University in addition to studying. All activities are held by students in the rules and supervision of the Administrative Bureau of Student and Alumni (BAKA). All student activities through the BAKA in the selection of student activities in order to create a creative and beneficial to the students themselves and the environment outside the university. Each selected activities must pass through several stages of selectors who have different places and with different activities as well. The problem that every proposal that created the students hampered by location, different activities and delivery processes of proposals from the selectors to the other selectors going slowly. Based on the background of the existing problems, the authors designed a system that can help the process of working in the BAKA. The system was designed which includes three large scope, the proposal online, online activities and Accountability Sheet and SKKK online. The results which obtained from the application is the system can help the working process and accelerate the proposal approval process and Accountability Reports of all activities LK. Results of questionnaire indicate that there are features in the application is in conformity with the needs of BAKA.